PEMETAAN GEOLOGI DESA SUNGAI PAUR, KECAMATAN RENAH MENDALUH, KABUPATEN TANJUNG JABUNG BARAT, JAMBI - Nurul Izzah Asral Asral; Yudhi Achnopha; Bagus Adhitya (JOURNAL ONLINE OF PHYSICS, 2021)
Geological mapping is one of the methods to study the geological state of an area, in addition to studying it from existing literature. In geological mapping discussed about the condition of geomorphology, stratigraphy, geological structure so that the results of the overall geological conditions and recommendations in the form of potentials and disaster-prone areas in the research area. The research area located in Sungai Puar Village, Renah Mendaluh District, Tanjung Jabung Barat Regency, Jambi Province is included in the South Sumatra Basin, where the basin was formed from extensional tectonics at the beginning of the Late Eocene. Stratigraphically in the research area there are Oligocece - Early Miocene Talangakar Formations and Early - Late Miocene-aged Gumai Formations. Regional stratigraphically the stratigraphic relationship of these two formations is in harmony with the deposition environment of the transitional Talangakar Formation – shallow sea, while for the Gumai Formation it belongs to the shallow marine deposition environment. The purpose of this research is to know the geological condition of the research area. In the method used for data analysis is the geological mapping method itself.